Curcumin-Induced DNA Demethylation in Human Gastric Cancer Cells Is Mediated by the DNA-Damage Response Pathway. (17th June 2020) - Tong, Ruiying; Wu, Xian; Liu, Ying; Liu, Yang; Zhou, Jigang; Jiang, Xinying; Zhang, Li; He, Xiaoying; Ma, Libing
Abstract : Curcumin, a natural polyphenol antioxidant extracted from the root of turmeric ( Curcuma longa ), can induce apoptosis and DNA demethylation in several types of cancer cells. However, the mechanism of its anticancer potentials and DNA demethylation effects and the potential relationships between these outcomes have not been clearly elucidated. In the present study, the effects of curcumin on the proliferation, colony formation, and migration of human gastric cancer cells (hGCCs) were explored. Reactive oxygen species (ROS) levels, mitochondrial damage, DNA damage, and apoptosis of curcumin-treated hGCCs were analyzed. Changes in the expression of several genes related to DNA damage repair, the p53 pathway, cell cycle, and DNA methylation following curcumin treatment were also evaluated. We observed that curcumin inhibited the proliferation, colony formation, and migration of hGCCs in a dose- and time-dependent fashion. A high concentration of curcumin elevated ROS levels and triggered mitochondrial damage, DNA damage, and apoptosis of hGCCs. Further, curcumin-induced DNA demethylation of hGCCs was mediated by the damaged DNA repair-p53-p21/GADD45A-cyclin/CDK-Rb/E2F-DNMT1 axis. We propose that the anticancer effect of curcumin could largely be attributed to its prooxidative effect at high concentrations and ROS elevation in cancer cells. Moreover, we present a novel mechanism by which curcumin induces DNA demethylation of hGCCs, suggesting the need to further investigate the demethylation mechanisms of other DNA hypomethylating drugs.